2005
DOI: 10.1212/01.wnl.0000156351.72313.d3
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular telephones and risk for brain tumors

Abstract: The results do not support an association between use of cellular telephones and risk for glioma or meningioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 26 publications
(21 reference statements)
4
105
0
Order By: Relevance
“…The percentage of cases or controls exposed for at least 10 years in the above studies is 0% [16,[18][19][20], less than 5% [21,25,27,28], less than 10% [23,24,26,29], not given [30].…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The percentage of cases or controls exposed for at least 10 years in the above studies is 0% [16,[18][19][20], less than 5% [21,25,27,28], less than 10% [23,24,26,29], not given [30].…”
Section: Resultsmentioning
confidence: 81%
“…The editorial of Cardis and Sadetzki takes further the remarks by Saracci and Samet, and leaves little doubt about the relevance of our criticisms, which we document on as follows ( Table 1): • of the 17 Interphone studies [16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], fewer than 10% of the exposed cases and controls had completed at least 10 years of cellphone latency or continued use, which means that over 90% had an inadequate exposure time. Since in most of the tumours 95%CI superior limit < 1 for OR<1, and 95%CI inferior limit > 1 for OR>1; 2 ORs decrease together with the increase of exposition and/or latency; n.r.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Four studies from the INTERPHONE study showed no increased overall risk of glioma or meningioma in relation to regular mobile phone use (Christensen et al, 2004(Christensen et al, , 2005Hepworth et al, 2006;Schuz et al, 2006), although glioma risk increased non-significantly (OR ¼ 2.20; 95% CI: 0.94 -5.11) among long-term users (10 years or more), but no excess risk was found for temporal lobe tumours, considered to be exposed to the highest radio frequency (RF) -EMF (Schuz et al, 2006). In a Swedish study, the OR for glioma on the same side as mobile phone use increased to 1.8 (95% CI: 0.8 -3.9) among long-term (X10 years) mobile phone users, but the corresponding OR for glioma on the opposite side was found to decrease to 0.6 (95% CI: 0.3 -1.4) among long-term users (Lönn et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since only glial and meningial tissue close to the surface of the head is exposed to relatively high electromagnetic fields (EMFs) emitted from mobile phones, brain tumours, especially glioma and meningioma, have received particular attention, along with acoustic neurinoma and salivary gland tumours. To investigate whether mobile phone users have an increased risk for these tumours, a collaborative case -control study in 13 countries, the INTERPHONE study, was initiated in 2000, coordinated by the International Agency for Research on Cancer (IARC) and is still underway (Cardis and Kilkenny, 1999;Christensen et al, 2005;Lönn et al, 2005;Hepworth et al, 2006;Schuz et al, 2006;Takebayashi et al, 2006;Cardis et al, 2007;Hours et al, 2007). Some national reports are already published, with mixed findings.…”
mentioning
confidence: 99%